Mainstreaming diversity, equity and inclusion as future workplace ethics - Raimi, Lukman, 1971-; Kah, Jainaba M. L., 1970- (IGI Global, Information Science Reference, 2022)
"This book fulfills a need for academics and researchers to provide some veritable measures for evaluating the multicultural, plural, and monolithic organizations, where diversity, equity, and inclusion have been embraced"--